2024
DOI: 10.1097/ico.0000000000003460
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fuchs Corneal Endothelial Dystrophy Using Artificial Intelligence–Derived Morphometric Parameters From Specular Microscopy Images

Angelica M. Prada,
Fernando Quintero,
Kevin Mendoza
et al.

Abstract: Purpose: The aim of this study was to evaluate the efficacy of artificial intelligence–derived morphometric parameters in characterizing Fuchs corneal endothelial dystrophy (FECD) from specular microscopy images. Methods: This cross-sectional study recruited patients diagnosed with FECD, who underwent ophthalmologic evaluations, including slit-lamp examinations and corneal endothelial assessments using specular microscopy. The modified Krachmer grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This methodology was consolidated in 2023 with a novel approach to codify cells and guttae. Recently, Prada et al 13 reported that using convolutional neural networks for the evaluation of specular microscope images from patients with FECD revealed a correlation between the proportion of guttae area (referred to as guttae area ratio %—GAR%) and the modified Krachmer clinical grading. This finding suggests the potential utility of GAR% as an objective and quantitative assessment of FECD severity.…”
mentioning
confidence: 99%
“…This methodology was consolidated in 2023 with a novel approach to codify cells and guttae. Recently, Prada et al 13 reported that using convolutional neural networks for the evaluation of specular microscope images from patients with FECD revealed a correlation between the proportion of guttae area (referred to as guttae area ratio %—GAR%) and the modified Krachmer clinical grading. This finding suggests the potential utility of GAR% as an objective and quantitative assessment of FECD severity.…”
mentioning
confidence: 99%